Understanding effects of reality disjunction in communication between people living with dementia and their carers - care home study - Eraslan, Semanur (2024)
Reality disjunction refers to a phenomenon characterised by a mismatch between two individuals' perceptions on the events or conditions surrounding them. Reality disjunction often gives rise to behaviours, statements, or beliefs that diverge from those of others. Reality disjunction is common in dementia care, leading to difficulties in communication and the occurrence of challenging behaviour. Previous research on reality disjunction in dementia care has primarily focused on management strategies employed by carers. These studies have examined the strategies and discussed their applicability and acceptability in dementia care. However, there is limited research that investigate experiences of reality disjunction and factors, beyond carer strategies, that influence the management of reality disjunction.